Islamic Shariah Principles for Investment in the Indian Stock Market - Sulaiman H (Universitas Islam Negeri (UIN) Walisongo Semarang, 2026)
Purpose - The purpose of this study is to examine the scope of Shariah-compliant investment opportunities in the Indian stock market and to evaluate the principles, ethical criteria, and screening mechanisms used to identify permissible investment options under Islamic finance. Method - The study adopts a descriptive and analytical research approach based on secondary data collected from scholarly articles, financial reports, regulatory publications, and established Shariah screening frameworks. The analysis focuses on sector-based exclusions, financial ratio screening, and ethical investment criteria applied in stock selection. Result - The findings reveal that the Indian stock market provides meaningful opportunities for Shariah-compliant investing, particularly through screened equities and ethical mutual funds. However, the study identifies several barriers to wider adoption, including limited investor awareness, regulatory challenges, and restricted availability of diversified Shariah-compliant financial products. Implication - The study implies that strengthening institutional support, enhancing regulatory facilitation, and improving investor education can significantly promote the growth of Shariah-compliant investment in India. It also highlights the potential of Islamic finance as an ethical investment alternative within emerging financial markets. Originality - This study contributes to the existing literature by specifically analyzing the Indian stock market from the perspective of Shariah-compliant investment opportunities, integrating Islamic financial principles with practical stock screening mechanisms, and addressing the challenges affecting the expansion of halal investment options in the Indian context. Keywords: Islamic Finance, Shariah Investment, Halal Stocks, Indian Stock Market, Ethical Investing